2018
DOI: 10.1007/s10654-018-0358-z
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of parity on life course blood pressure trajectories: the HUNT study in Norway

Abstract: The drop in blood pressure during pregnancy may persist postpartum, but the impact of pregnancy on blood pressure across the life course is not known. In this study we examined blood pressure trajectories for women in the years preceding and following pregnancy and compared life course trajectories of blood pressure for parous and nulliparous women. We linked information on all women who participated in the population-based, longitudinal HUNT Study, Norway with pregnancy information from the Medical Birth Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…In our previous analysis on parity and life course blood pressure trajectories from this cohort, we observed that women with HDP as a group had higher blood pressure from before first pregnancy until beyond 60 years of age 18. In the present study, we examined a wide range of cardiovascular risk factors separately among women with preeclampsia and gestational hypertension.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In our previous analysis on parity and life course blood pressure trajectories from this cohort, we observed that women with HDP as a group had higher blood pressure from before first pregnancy until beyond 60 years of age 18. In the present study, we examined a wide range of cardiovascular risk factors separately among women with preeclampsia and gestational hypertension.…”
Section: Discussionmentioning
confidence: 73%
“…In the HUNT (Nord‐Trøndelag Health Study) cohort in Norway, we recently observed that higher blood pressure in women with a history of HDP manifests before first pregnancy and lasts beyond 60 years of age 18. In the present study, we examine the life course trajectories from before first pregnancy and until 60 years of age for a broad range of cardiovascular risk factors in women with and without HDP in their first pregnancy.…”
Section: Introductionmentioning
confidence: 96%
“…For additional EJE references please see [142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160].…”
Section: Main Results In the Last 3 Yearsunclassified
“…[16][17][18] Moreover, findings from prospective studies on this issue, all conducted in Western countries, were also limited and inconclusive. 6,[19][20][21] The current study aims at determining whether the live birth/parity number is an independent risk factor for hypertension development among Iranian women aged 30-70 years, with 13.5 years of follow-up, using a population-based cohort, the Tehran Lipid and Glucose Study (TLGS).…”
mentioning
confidence: 99%